Urgensi Regulasi Penggunaan Kecerdasan Buatan (AI) Dalam Ecommerce - Arum Prastyanti, Rina; Mustofa, Khoirul (Jurnal Bedah Hukum, 2024)
AI influences the facility's algorithm or search engine for a particular product or service. Then it changes the cost and length of lines such as in online transport, which can be detrimental to customers. Not to mention about data security and consumer privacy in the era of frequent cybercrime. In Indonesia, consumers' personal data is spread or sold due to hacking in many e-commerce applications. The juridical-normative method is used in this research to determine consumer protection after the implementation of AI in online businesses. The purpose of this study is to determine the urgency of regulation of the use of artificial intelligence (AI) in e-commerce. And the form of legal protection for consumers of e commerce users. This research uses two approaches: a case approach and a statutory approach, all available data is analysed using qualitative descriptive analysis techniques, Taking into account that the use of AI in Indonesia will not only increase for technological purposes alone, but also in various sectors, existing laws and regulations in the field of technology must be applied to regulate the application of AI in Indonesia. Any new regulation should ensure compliance with existing regulations and adjust to the characteristics of the relevant sectors